2015
DOI: 10.1002/14651858.cd002271.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous distending pressure for respiratory distress in preterm infants

Abstract: Cochrane Database of Systematic Reviews Data collection and analysis We used standard methods of The Cochrane Collaboration and its Neonatal Review Group, including independent assessment of trial quality and extraction of data by each review author. Main results We included six studies involving 355 infants-two using face mask CPAP, two CNP, one nasal CPAP and one both CNP (for less ill babies) and endotracheal CPAP (for sicker babies). For this update, we included no new trials. Continuous distending pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 35 publications
(57 reference statements)
1
50
0
2
Order By: Relevance
“…These guidelines recommend the use of nasal prongs as a mechanism of delivery, and a flow rate of 0.5–1 L/min, increasing to 2 L/min in severe respiratory distress to achieve an oxygen saturation of >90%. Studies in high-income countries in the 1970s suggested a survival advantage for preterm newborns with severe respiratory distress managed with CPAP compared with standard oxygen therapy (relative risk 0.52, 95% CI 0.32 to 0.87) 21. Since then, the use of CPAP has increased and become a standard of care for preterm newborns with moderate to severe respiratory distress, in tertiary and many non-tertiary hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These guidelines recommend the use of nasal prongs as a mechanism of delivery, and a flow rate of 0.5–1 L/min, increasing to 2 L/min in severe respiratory distress to achieve an oxygen saturation of >90%. Studies in high-income countries in the 1970s suggested a survival advantage for preterm newborns with severe respiratory distress managed with CPAP compared with standard oxygen therapy (relative risk 0.52, 95% CI 0.32 to 0.87) 21. Since then, the use of CPAP has increased and become a standard of care for preterm newborns with moderate to severe respiratory distress, in tertiary and many non-tertiary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries, the safety profile of bubble CPAP appears similar to that of CPAP produced by other means (eg, ventilator-driven CPAP), and the majority of reported complications can be mitigated or prevented by adequate nursing care 16 21 24…”
Section: Introductionmentioning
confidence: 99%
“…However, as respiratory support in the delivery room includes providing support to clear airway liquid, which is not a requirement days after birth, higher CPAP levels are likely to be needed immediately after birth. Similarly, higher CPAP levels may be required to prevent return of lung liquid and maintain functional residual capacity [8, 24-27]. In recent years it has become increasingly apparent that assuming strategies that are effective in the NICU (hours to days after birth) will be equally effective in the delivery room, ignoring much of what we know about the fetal to neonatal transition.…”
Section: The Larynxmentioning
confidence: 99%
“…Together, these conclude that early CPAP results in a small but statistically significant reduction in the composite outcome of bronchopulmonary dysplasia and/or death 3–5. Additionally, these trials indicate that CPAP reduces the need for mechanical ventilation and shortens the duration of supplemental oxygen exposure 4 6…”
Section: What Is the Strength Of Evidence For The Use Of Cpap To Treamentioning
confidence: 99%
“…In a multicentre RCT comparing early CPAP to oxygen therapy with or without mechanical ventilation in 12 South American centres, the risk of mortality, albeit not significantly, was lower in the CPAP-treated group (RR 0.72; 95% CI 0.41 to 1.25). In a Cochrane review, CPAP use was associated with a significant reduction in mortality (RR 0.52; 95% CI 0.32 to 0.87) and none of the included trials raised concern for increased mortality risk 6. Although the majority of the studies included in the Cochrane were conducted over 30 years ago in developed countries, no significant evidence to date suggests that CPAP use will increase mortality.…”
Section: Are There Relevant Differences Between Studies Conducted In mentioning
confidence: 99%